Peran Sustainability Business Strategy dalam meningkatkan Business Sustainability - Tugiantoro; Ida Adhani (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This research aims to find out whether the Sustainable Business Strategy established by the organization can improve Business Sustainability. Sustainable development is the UN agenda for 2030 in the Sustainable Development Goals (SDGs) which covers various issues and takes advantage of progress in the field of sustainable development. The research was conducted with a series of online literature studies using qualitative methods based on a phenomenological approach, and explained using a conceptual framework. Based on research, the implementation of a Sustainable Business Strategy in an organization to be successful must be applied to organizational culture, implemented by operations sustainability, applying digital technology, in organizational operations implementing ESG (Environmental, Social, and Governance), implementing ESG Governance and ESG Risk, in management and reporting implements sustainability accounting and sustainability reporting. The research results show that a Sustainable Business Strategy is able to increase Business Sustainability/Company Sustainability. This research also provides an input framework for decision makers, academics, and business managers in taking a strategic approach to the Company, to implement a Sustainable Business Strategy to achieve Business Sustainability/Corporate Sustainability.